Hepatic encephalopathy and spontaneous bacterial peritonitis are associated with increased liver-related readmissions in cirrhosis - Wang, Shan; Zhang, Lin; Li, Jin; Feng, Jiajun; Gao, Jie; Huang, Rui (Frontiers in Medicine, 2025)
IntroductionLiver disease remains a significant global health concern. In China, the number of patients with liver cirrhosis is estimated to reach 7 million. In addition to the high risk of death, cirrhosis leads to several severe complications. Patients with cirrhosis have significantly longer hospital stays and higher total hospital costs than those without cirrhosis. We aimed to investigate the predictors of readmission among patients with cirrhosis in China.Materials and methodsWe conducted a retrospective study to evaluate adult patients with cirrhosis. Data on various sociodemographic, clinical, and hospitalization characteristics were collected. We defined the primary endpoint as the first liver-related readmission occurring within 30–90 days of initial hospitalization. Adult patients with cirrhosis admitted to our hospital between January 2009 and December 2022 were included. Differences between groups were analyzed using Student’s t-test and chi-square test. Logistic and multiple linear regression analyses were performed to identify predictors associated with readmission and the length of the first hospitalization.ResultsIn total, 1,285 patients were diagnosed with cirrhosis. Among these patients, 767 (59.7%) were males, and the mean age was 58.9 ± 12.3 years. Seventy-two (5.6%) and 154 (12.0%) patients were readmitted within 30 and 90 days, respectively. Compared with those who were not readmitted, patients readmitted at 30-day and 90-day had a higher proportion of males, ascites, spontaneous bacterial peritonitis, electrolyte abnormalities, higher Child-Pugh–Turcotte scores, longer initial hospital stays, and higher initial hospitalization costs. Logistic regression analysis indicated that hepatic encephalopathy, spontaneous bacterial peritonitis, diabetes, and ascites were predictors of 30- and 90-day readmission. Hypertension and spontaneous bacterial peritonitis were significant predictors of the length of the first hospitalization.ConclusionPatients with cirrhosis presenting with hepatic encephalopathy, ascites, and spontaneous bacterial peritonitis may have a higher risk of rehospitalization.